Melacak Jejak Radikalisme dalam Islam: Akar Ideologis dan Eksistensinya dari Masa ke Masa - Sony Amrullah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
Radicalism is an extreme attitude shown in the effort to defend ideology. Radicalism is often accompanied by extreme attitudes such as violence, coercion, and terror to groups that are considered opposed to their ideology. Historically, Islam has also given birth to people who are disproportionate in religion so they can be called as radical figures and groups in Islam. Traces of radicalism in Islam can be traced its existence even starting from the early formation of Islam that is the period of propagation of the Prophet Muhammad SAW. This extreme attitude then continues to live and evolve and even establish its existence by forming a particular group. Ironically, this radical group that pursues the purification of Islam is alive and growing to this day. This paper seeks to explore traces of Islamic radicalism from the period of the Prophet Muhammad SAW, the period of companions, to the contemporary period.